Efficacy of Non-Surgical Periodontal Therapy with Azithromycin in Chronic Periodontitis: A Quasi-Experimental Study - Khan, Wajiha; Bakht, Khush (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the effectiveness of non-surgical periodontal therapy alone versus in combination with Azithromycin in improving mean probing pocket depth (PPD) and mean clinical attachment level (CAL) in patients with moderate to severe chronic periodontitis. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Periodontology, Khyber College of Dentistry, Peshawar, Pakistan, from Oct 20 to Apr 21. Methodology: A total of 70 patients with chronic periodontitis were randomly assigned into two groups: Group-A received scaling and root planing alone, while Group-B received scaling and root planing with adjunctive Azithromycin. Periodontal parameters including PPD and CAL were assessed using a William’s probe at baseline and three months post-treatment. Results: Group- B showed significantly better clinical outcomes than Group-A. The mean PPD in Group-B was 2.44±0.24 mm compared to 3.43±0.15 mm in Group-A (p=0.020). Similarly, the mean CAL in Group-B was 0.34±0.09 mm versus 0.40±0.10 mm in Group-A (p-value 0.020), indicating a statistically significant improvement in both parameters. Conclusion: Adjunctive use of Azithromycin with non-surgical periodontal therapy resulted in significant improvements in probing pocket depth and clinical attachment level. These findings support the selective use of systemic antibiotics in the management of chronic periodontitis to enhance clinical outcomes.